Major Depressive Disorder as a Condition Negatively Impacting Both Mental and Physical Functioning. What to Do When There Is Treatment Resistance? - Makar, Monika; Michałka, Daria; Gałuszka, Zuzanna; Papachristoforou , Natalie; Głowacka, Justyna; Kocjan, Aleksandra; Bąk, Emilia; Tekiela, Natalia; Chmiel, Radosław; Bartuś, Tomasz (Quality in Sport, 2025)
The objective of this article is to assess the efficacy and safety of diverse therapeutic strategies for treatment-resistant depression (TRD), encompassing both pharmacological and non-pharmacological interventions. Additionally, the review identifies potential avenues for future research within this domain. The article compares the results of selected studies. We conducted a literature search in November of 2024, using PubMed. Six studies were identified, chosen, and appraised. Among these studies, three are systematic reviews and three are narrative literature reviews. If it comes to treatment efficacy studies have demonstrated the effectiveness of several strategies. Ketamine and esketamine have shown rapid and substantial efficacy in mitigating the symptoms of TRD. Augmentation with aripiprazole and quetiapine has also been found to enhance the response to antidepressant treatment. The combination of olanzapine and fluoxetine is effective for treating TRD, however, it may be associated with metabolic side effects. Augmentation with lithium, triiodothyronine (T3), and lamotrigine shows promising results, though further research is required to fully evaluate their efficacy and safety in TRD management. The management of TRD is associated with several challenges. These include the absence of a standardized definition and grading system, which impedes the comparison of research outcomes. The multifactorial nature of TRD further complicates the development of a universal treatment strategy. Summarizing, there are several treatment strategies available for TRD, however, the most effective approach should be personalized for each patient. Ongoing research is critical to advancing our understanding of TRD and developing more effective therapeutic options.